The Relationship Behavior Of Treat The External Genital Organs With Incidence Of Vulvovaginitis During Menstruation In Adolescent Girls - Nuraini, Nanik; Hasanah, Nur; Habibah, Hani (Jurnal MIDPRO, 2024)
The problem of reproductive health disorders that is often found in teenagers during menstruation is the behavior of caring for the external genitalia organs incorrectly, so that many teenagers experience vulvovaginitis during menstruation. The aim of the research was to determine the relationship between external genital organ care behavior and the incidence of vulvovaginitis during menstruation in class VII teenage girls at MTsN Manyar. The design of this research was cross sectional analytical correlation with a population of all class VII female students, 118 respondents, so that a sample of 91 respondents was obtained. The sampling technique used Simple Random Sampling and data collection using a questionnaire sheet, while the statistical test used was Spearman rho. The results of the research showed that the majority of young women behaved well in caring for their external genital organs, 48 ​​respondents (52.7%), the majority of young women did not experience irritation, 35 respondents (38.5%), and young women behaved well in caring for their external genital organs and did not experience irritation. irritation of 31 respondents (88.6%). Based on the Spearman rho test, the p value = 0.000 (<0.05), meaning there is a relationship between the behavior of caring for external genital organs and the incidence of vulvovaginitis in adolescents. It is hoped that MTsN Manyar students will receive education for young women about women's reproductive health through biology lessons.